CD-ROM-based training in hazard control - Riipinen, Hannu; Andersson, Ing-Marie; Rosén, Gunnar (SJWEH Supplements, 2005)
Two international workshops on airborne dust control were arranged in March 2003, one in Cape Town and the other in Johannesburg, South Africa. The aim of the courses in the workshops was to test new CD-ROM-based training material on airborne dust control. The material uses visualization methods in video clips to illustrate the contents. On the basis of feedback from the courses, the training material was revised to make it accessible to all appropriately qualified teachers. The CD-ROM-based material and the utilized visualization methods provide a powerful tool for transferring knowledge of occupational hygiene and dust prevention globally. To ensure the quality of the visual presentation and to make such material as user-friendly as possible, the photographing, videoing, and formatting of the material should be handled with expertise.
Keywords: aerosol; CD-ROM; Compact Disc Read-Only Memory; dust; hazard control; occupational hygiene; Pimex; training; video; visualization